G48(P) Incidental findings in mri-enterography in paediatric patients diagnosed with inflammatory bowel disease. (12th March 2018) - Basheer, N; Kanumakala, SH; Butt, A; Lavanya, V
Abstract : Aims: Although coincidental findings in inflammatory bowel disease (IBD) patients detected on MRI-enterography (MRE) have been extensively discussed in the adult population, only very few papers have discussed such findings in children. The primary aim of this study was to determine the frequency of incidental findings detected in children with confirmed IBD undergoing MRE for diagnostic/staging purposes. The secondary aim of the study was to evaluate the clinical impact of such incidental findings. Methods: All MRE performed at a single centre from January 2014 to December 2016 were retrospectively analysed; only patients with a confirmed diagnosis of IBD were included. A random selection of MRE without incidental findings was reviewed by a consultant radiologist to inform that incidental findings were not missed previously (double reporting). The medical notes of children with incidental findings were retrospectively reviewed to inform the clinical impact of such findings. Results: A total of 190 patients underwent MRE over the three years, but 102 patients with a confirmed diagnosis of IBD were only included. Incidental findings were noted in 16 patients (15.6%); two were intestinal findings (probable small bowel intussusception) and the rest were extra intestinal findings. 50% (8 patients) of the incidental findings related to renal pathology (solitary kidney, cyst, duplex kidney, dilated pelvicalyceal system), 18.7% (3 patients) to spleen pathology (splenomegaly, cyst), 12.5% (2 patients) to prominent mesenteric lymphadenopathy, and 6.2% (1 patient) to gallbladder pathology (gallbladder stones) respectively. In 7 patients (43.7%) (1 with kidney cyst, 2 with duplex kidney, 2 with dilated pelvicalyceal system, 2 with splenomegaly), further imaging studies (ultrasounds) were done. Incidental findings were re-confirmed in 4 of them; one patient with prominent splenomegaly required further haematology investigations and the other 3 patients with renal pathologies (1 with duplex kidney, 2 with dilated pelvicalyceal system) did not require further investigations. Conclusion: Incidental and unrelated findings were found in 15.6% of IBD patients undergoing MRE. Although many (43.7%) of these children required further imaging studies, only one patient from the entire cohort (1%) (massive splenomegaly) needed further investigations for a significant, previously unidentified pathology.